Otimização e análise da localização de Unidades de Saúde da Família do município de João Pessoa - Silva, Ana Nery Nascimento (2023)
The Family Health Strategy has as its main objective the reorganization of Primary Health Care in the country, in accordance with the principles of the Unified Health System, and is considered by the Ministry of Health as a strategy for expansion, quality and consolidation of Primary Health Care in Brazil. Thus, the Family Health Units, the main "gateway" of the Unified Health System and the basis of the Family Health Strategy, must provide a quality and effective service. This descriptive and quantitative study, with the aim of optimizing/covering the care provided to users of the Family Health Units, that is, the population, in the city of João Pessoa - PB, aims to analyze the network of service provided by the USFs in the municipality of João Pessoa - PB in two aspects: first looking at the healthcare network in the city of João Pessoa - PB as a graph and analyzing its centrality measures. And then applying the Maximum Coverage Location Problem in order to verify the minimum amount of USFs necessary for the system to have a coverage of 100%. Next, data from the Health Care Network obtained from the Municipal Health Department were analyzed in order to assess the coverage area of the Health Care Network in order to maximize the coverage area of the current public health network of João Pessoa - PB, aiming to facilitate users’ access to services, reducing the distance between the individual’s residence and the health services provided by the USFs.